THE INFLUENCE OF INNOVATIVE ATTITUDES AND DISCIPLINE ON TEACHERS’ PEDAGOGICAL COMPETENCE IN THE CLUSTER OF SD INPRES TALA-TALA KECAMATAN BISSAPPU KABUPATEN BANTAENG - Saripati Bunga Alam; Nursalam; Idawati; Sulfasyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the innovative attitude of teachers at the cluster of SD Inpres Tala-Tala, Kecamatan Bisssappu, Kabupaten Bantaeng. This research was an Ex Post Facto research. The population in this study was teachers at the cluster of SD Inpress Tala- Tala, Kecamatan Bissappu, Kabupaten Bantaeng, which consisted of eight elementary schools. The study was a descriptive correlational method. The population and sample of this study consisted of 64 teachers who were selected by using saturated sample because the population was less than 100 people. The data were collected by administering using a questionnaire on the teacher's innovative attitudes. Then, the data were analyzed by using descriptive techniques. The results of the study showed that the maximum value of innovative attitudes was a 110 while the minimum value was 80. Then, the average value was 98.3125 and the standard deviation was 5.77591. Based on the results of the innovative attitude interval, 8% of respondents in low category gave a score between 80-90; 30% of the respondents in the medium category gave a score between 91-100, while in the high category, 26% of respondents scored between 101-110.